2022
DOI: 10.3390/vaccines10081271
|View full text |Cite
|
Sign up to set email alerts
|

Are Fear of COVID-19 and Vaccine Hesitancy Associated with COVID-19 Vaccine Uptake? A Population-Based Online Survey in Nigeria

Abstract: This study examined the association between COVID-19 and fear of contracting COVID-19 and reasons for vaccination refusal. A population-based online survey was conducted via social media in Nigeria using the Fear of COVID-19 scale and items related to vaccination refusal/hesitancy items. Individuals aged 13 years and older were invited to participate. Data were analysed using binary logistic regression to calculate odds ratios (ORs) and associated 95% confidence intervals (CIs) at a p-value of less than 0.05. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Omar and Hani [59] reported the highest VH rate (54% in Egypt) for uptake of the COVID-19 vaccine. The subsequent studies reported that participants had been vaccinated against COVID-19 [30,35,40,50,52,61]. Of those three studies [35,50,61], it was indicated that above 50% of their participants were vaccinated with at least one dose.…”
Section: Intention To Uptake Covid-19 Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Omar and Hani [59] reported the highest VH rate (54% in Egypt) for uptake of the COVID-19 vaccine. The subsequent studies reported that participants had been vaccinated against COVID-19 [30,35,40,50,52,61]. Of those three studies [35,50,61], it was indicated that above 50% of their participants were vaccinated with at least one dose.…”
Section: Intention To Uptake Covid-19 Vaccinesmentioning
confidence: 99%
“…Thirty-three studies (n = 33) highlighted the barriers associated with COVID-19 vaccine uptake. Of those twenty-nine studies (n = 29) cited fears over potential side effects and the newly developed vaccine being unsafe for the African population [27,29,30,[32][33][34][35][36][37][40][41][42][43][44][45]48,50,[54][55][56][57][58][59][60][61][62][63][64].…”
Section: Barriers To the Uptake Of The Covid-19 Vaccinementioning
confidence: 99%
See 1 more Smart Citation
“…“Vaccine hesitancy” refers to the public's indecisive attitude toward vaccination, an intermediate state between total acceptance and strong resistance known as vaccine denial ( MacDonald & Hesitancy, 2015 ). Conspiracy theories, misunderstandings, and questions about side effects may turn vaccine hesitancy into vaccine denial ( Chutiyami et al, 2022 ). However, evidence-based communication and effective media organization strategies may convert vaccine denial to vaccine hesitancy and then mass vaccination ( Khubchandani et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conceptual frameworks such as the "three Cs model of vaccine hesitancy" indicate that complacency or low perceived risk of vaccine preventable diseases as well as convenience (e.g. availability and acceptability) and confidence (or trust) are the main factors that influence vaccine hesitancy (22,23). Of note, 44.4% of Jamaica's participants were willing to be vaccinated, if available, suggesting that "convenience" or accessibility of COVID-19 vaccines may have contributed to the low uptake despite the establishment of fixed vaccination sites across the island.…”
Section: Discussionmentioning
confidence: 99%